PENGARUH KUALITAS DESAIN SERTA HARGA TERHADAP KEPUTUSAN PEMBELIAN MOBIL HYUNDAI PADA PT ASIA MOBIL INTERNATIONAL DI SAMARINDA - Deni Ari Firmanjaya (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
Deni Ari Firmanjaya. This study aims to determine the quality, design and price of the Purchase Decision PT Hyundai Mobil. Asia Mobil International in Samarinda. Where the proposed three independent variables and the dependent variable, namely the quality, design and price act as independent variables and buying decisions serve as the dependent variable.This research was conducted by questionnaire to the consumer automobile and analyzed with regression. The first phase test validity and reliability of each variable. The second phase, regression of variable quality, design and price of the buying decision.The results showed that all of these variables together - the same influence on purchase decisions, but the design variables more dominant influence on buying decisions